Program Imtaq: Upaya Menumbuhkan Aspek Spiritualitas Siswa di MIS YASIM Karumbu Bima - St. Asni; Muammar Qadafi (UIN Mataram, 2023)
The spiritual aspect is a problem that continues to be a concern at the Private Madrasah Ibtidaiyah (MIS) YASIM of Karumbu considering the decline in spiritual values ??that occur in children. This study aims to describe the Friday Imtaq program which is encouraged by teachers in order to foster spiritual values ??in students. This study uses a qualitative approach with a case study type using interviews, observation, and documentation as data collection techniques. The results show that the Thursday and Friday Imtaq program carried out at MIS YASIM Karumbu is filled with various activities including: reciting the Koran, practicing obligatory and sunnah prayers, and memorizing prayers and short letters. This program received a very good response from students as shown by the enthusiasm of students in participating in the program twice a week.